The Diagrams in the Cartography of "El Deseo Invisible" by Gonzalo Azalar - Núñez Cristino, Cristian (Nomadías, 2025)
From reading "El deseo invisible" by Gonzalo Asalazar (2017), I aim to develop the concept of Sentimental Cartography as defined by Suely Rolnik (1989). This cartography evolves and is constructed while certain worlds disintegrate and others form to express contemporary affections, rendering existing universes obsolete. Asalazar proposes the map of downtown Santiago as a layout that, unlike others in the city and country, has remained more or less intact since the colonial era. It is upon this layout that another cartography emerges, which challenges the official one and is driven by desire. Adding contributions from Foucault, Deleuze, Barrales, Fernández, and others, I intend to develop the concept of the diagram as a weapon in the power struggle; and on the other hand, delve into a potential map of violence that cuts across recorded events, culminating from the civic-political-military dictatorship (1973-1989), and that can be applied to other territories victimized by violence from power structures, attempting to dismantle a narrative that imposes forgetfulness and painless amnesia, through the denial of the catastrophic nature of the event and the suppression of the most atrocious memories (Santos 2019).